Exploring the Influence of Equity Perception on Homestead Withdrawal Intention of Farmers: An Empirical Investigation - Zhu, Xiaogang; Zhang, Xuan (Transformations In Business & Economics, 2026)
Promoting the orderly withdrawal of idle homesteads is a key strategy for optimizing the allocation of urban and rural land resources and advancing rural revitalization. A crucial factor in this process is the intentions of farmers. Previous studies have investigated the factors influencing the withdrawal intention of farmers from multiple perspectives, such as risk perception, family characteristics, resource endowment, and operational mechanisms. However, systematic empirical research on the compensation standards that farmers are most concerned about, particularly the underlying mechanisms of equity perception, is lacking. Therefore, a three-dimensional (reasonable consideration–horizontal equity–vertical equity) analytical framework was constructed based on Adams’s Equity Theory. An empirical analysis was conducted using a binary Logit model, drawing on survey data from 1236 questionnaires involving farmers in rural areas of Henan Province. Results reveal the following: (1) Farmers display high sensitivity to equity in withdrawal decision-making, with equity perceptions across all three dimensions being positively correlated with withdrawal intention. (2) Compared with the absolute amount of compensation, farmers place greater importance on “relative equity” (horizontal equity and vertical equity). (3) Among the control variables, rural household registration, degree of policy awareness, and presence/absence of a town house are significantly positively correlated with withdrawal intention, while age, dependence on agricultural income, and homestead remoteness are negatively correlated with withdrawal intention. Accordingly, policy recommendations include the introduction of a third-party assessment, formulation of graded compensation standards, and diversification of compensation modes. These recommendations aim to effectively facilitate the orderly withdrawal of idle homesteads by strengthening the positive equity perception of farmers. Overall, this study provides a theoretical basis and empirical support for improving homestead withdrawal compensation policies and offers valuable insights for promoting rural land system reforms.